Water Antenna - Ikhwan, Nur Iwana Mohd (Universiti Sains Malaysia, 2017)
Water antennas is a type of liquid antennas, which have become the most popular in recent years. They have appeared to be alternatives to traditional antennas for many applications especially in naval, maritime communication and wireless communication. The purpose of this thesis is to present an exhaustive study about water antenna, aiming at obtaining a better understanding of water antennas that utilizing liquid. The upper and the bottom (base) part of the water antenna is made up from an acrylic material. The acrylic cylinder is chosen due to its transparency. The specifications of the acrylic tube are; height=200mm, thickness=2mm, and diameter=2mm. FR4 is used as the substrate and copper is used as the ground plane with a circular shape and dimension of 100x100mm. The acrylic base has the same dimension as the substrate and copper. Most of the traditional water antenna are using a pure water and sea water as the medium of the antenna because it is low cost and easily accessible. The traditional water antenna usually has a low-performance level where its resonant frequency and radiation efficiency are low and the bandwidth is narrow. Therefore, the aim of this project is to design a water antenna that has a better performance compared to traditional water antenna. Various type of liquids is sampled and analyzed in terms of its resonant frequency and bandwidth such as pure water, distilled water, mineral water, sugar syrup, salt water, sea water, rain water, river water, and “zam zam” water. The resonant frequency, bandwidth, gain, and radiation pattern are of particular interests. The volume of the water in the acrylic tube is adjusted in order to tune the resonant frequency. The analysis is done by using the RF equipment for each 20mm with a range of 0-180mm water level. Based on the measurement that had been carried out by using the Network Analyzer, distilled water was chosen as the medium to design the antenna since it has the widest bandwidth and high resonant frequency. For instance, by using 20mm of distilled water the antenna could have a high resonant frequency which is 2.728GHz, return loss at -15.76